(untitled) (Itinera, 2025)
Walter Benjamin’s seminal 1923 essay «Die Aufgabe des Übersetzers» (The Task of the Translator) provides one of the most profound philosophical frameworks for understanding translation as a transcendent act that reveals the «pure language» underlying all human expression. In the era of large language models (LLMs) and neural machine translation, Benjamin’s concepts of textual «afterlife», linguistic kinship, and the philosophical versus practical divide in translation take on unprecedented urgency. This essay examines how the scaling of intelligence – from Qwen2.5-32B to 72B parameter models – simultaneously approaches and reveals the fundamental limitations of computational approaches to translation, particularly in the context of classical Chinese texts. Through analysis of contemporary scaling laws, linguistic challenges specific to classical Chinese, and emerging human-machine collaborative frameworks, this work argues that effective translation in the AI era requires what The Economist termed «cyborg translation» – a synergy that preserves human interpretive authority while leveraging machine computational power. The essay demonstrates that while scaling laws show diminishing returns and performance plateaus, the integration of philosophical understanding with technical innovation offers pathways toward translation systems that honor both Benjamin’s transcendent vision and practical computational constraints.